2000
DOI: 10.2134/jeq2000.00472425002900060042x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extraction Pretreatment on Radial Variation of Nitrogen Concentration in Tree Rings

Abstract: Past research in the paleoenvironmental subdiscipline of dendrochemistry has concluded that N concentration variation in tree rings cannot provide information on past conditions of environmental availability of N. The objective of this study was to test wood extraction pretreatments to remove wood extractives and sap, both of which may obscure the environmental signal of N availability in tree rings. Three increment cores were collected from each of six trees (three ponderosa pines and three Douglas‐firs). Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 0 publications
4
44
1
Order By: Relevance
“…Soluble N forms were extracted in a Soxhlet apparatus for 4 h in a mixture of toluene and ethanol 1:1, then in 100% ethanol for the same time, and then 1 h in distilled water, according to the protocol named "short duration" described by Sheppard and Thompson [21]. The samples subjected to this extraction are referred to as treated wood (TW), and the samples which had not been extracted are referred to as non-treated wood (NTW) in the following.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Soluble N forms were extracted in a Soxhlet apparatus for 4 h in a mixture of toluene and ethanol 1:1, then in 100% ethanol for the same time, and then 1 h in distilled water, according to the protocol named "short duration" described by Sheppard and Thompson [21]. The samples subjected to this extraction are referred to as treated wood (TW), and the samples which had not been extracted are referred to as non-treated wood (NTW) in the following.…”
Section: Methodsmentioning
confidence: 99%
“…Enough N remained for isotopic and elemental analyses. Sheppard and Thompson [21] report that mainly soluble forms of nitrogen are likely to have been removed by the treatment applied, considering the structural forms are mostly incorporated and crosslinked to lignin and are insoluble in organic solvents and water. However it is possible that an exchange of N from the storage pool into the…”
Section: Nitrogen Concentration and C/n Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…The high levels of N removed from rings, and the significance of the shift in δ 15 N post-extraction led the authors to conclude that extraction was necessary for interpreting temporal δ 15 N patterns in this system (Drake et al 2011). No wood N study has specifically tested which N compounds extraction may remove from or retain in ring wood. There is no N-containing compound that is easy to identify and purify, like cellulose for C. Presumably, N stored as proteins adhered to structural compounds (cellulose and lignin in cell walls) will be retained, while non-structural compounds (tannins, polyphenols, fats, waxes, resins, alkaloids) will be removed by extraction (Sheppard and Thompson 2000;Elhani et al 2003). The fact that extraction will remove non-nitrogenous soluble compounds as well as nitrogenous ones may be beneficial as it can increase extracted wood [N], potentially reducing analytical error (Sheppard and Thompson 2000).…”
Section: To Extract or Not Extractmentioning
confidence: 99%
“…There is no N-containing compound that is easy to identify and purify, like cellulose for C. Presumably, N stored as proteins adhered to structural compounds (cellulose and lignin in cell walls) will be retained, while non-structural compounds (tannins, polyphenols, fats, waxes, resins, alkaloids) will be removed by extraction (Sheppard and Thompson 2000;Elhani et al 2003). The fact that extraction will remove non-nitrogenous soluble compounds as well as nitrogenous ones may be beneficial as it can increase extracted wood [N], potentially reducing analytical error (Sheppard and Thompson 2000). Drake et al (2011) are the only authors to analyze extracted compounds, and reported that extracted sap exhibited δ 15 N values nearly 20 ‰ lower than extracted wood, although the mechanism for this difference was not determined.…”
Section: To Extract or Not Extractmentioning
confidence: 99%